The portrayal of patriarchal culture through mother and daughter characters in a silent film The Impossible Dream (1983) - Farida Faatin Naza (Passage: Journal of English Language and Literature, 2024)
Patriarchal culture is a social practice that places men as superior and women as inferior. In practice, patriarchal culture oppresses and exploits women. The Impossible Dream (1983) is a silent film that explores the issue of patriarchal culture, which is considered a woman's voice against the patriarchal system in society. This research aims to analyze the portrayal of patriarchal culture in the film, specifically through mother and daughter characters and to analyze the portrayal of children characters who imitate their parent's behavior based on gender using the theory of patriarchy by Walby (1990). The qualitative descriptive method with textual and visual analysis was employed to gained the data. The results of this research show three structures of patriarchal, namely the production of household, paid work, and culture that are portrayed in the film. This research also shows the behavior of daughter and son tends to be different because they imitate the behavior of parents based on their gender. Apart from women being oppressed and exploited, this research proves that patriarchal culture creates a double burden that is accepted by women. In addition, the patriarchal culture has an impact on children's behavior, thus children are implanted with the mindset of a patriarchal society from childhood. This research will contribute to the study of patriarchal in society. By conducting this research, the author hope it would shed a new understanding in the topic of patriarchy.